2012
DOI: 10.1902/jop.2011.110562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anxiety on Pain Perception Associated With Periodontal and Implant Surgery in a Private Practice

Abstract: For periodontal surgery and implant treatments pain perception is affected by the level of presurgical anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 42 publications
9
63
1
9
Order By: Relevance
“…It is well known that pre-procedural anxiety is related to increased levels of perceived pain for patients undergoing restorative dental treatment, such as periodontal treatment and implant placement (Klages et al 2006;Fardal & McCulloch 2012). Within orthodontics, Bergius et al (2008) reported that following the placement of orthodontic separators, patients who scored higher on the Dental Anxiety Scale (DAS) reported higher levels of pain than those with a lower DAS score (Bergius al.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pre-procedural anxiety is related to increased levels of perceived pain for patients undergoing restorative dental treatment, such as periodontal treatment and implant placement (Klages et al 2006;Fardal & McCulloch 2012). Within orthodontics, Bergius et al (2008) reported that following the placement of orthodontic separators, patients who scored higher on the Dental Anxiety Scale (DAS) reported higher levels of pain than those with a lower DAS score (Bergius al.…”
Section: Discussionmentioning
confidence: 99%
“…Anksiyete değerlendirilme yöntemlerinden biri de stres ölçümüdür. Stresin değerlendirildiği çalışmaların ikisinde tükürük kortizol seviyesine bakılmış başka bir çalışmada ise tükürük CgA (Kromogranin A) seviyesine bakılmış ve ortostatik tolerans testi uygulanmıştır (18,26,27). Tükürük kortizol seviyesi bir çalışmada ameliyattan bir hafta önce, ameliyat günü ve cerrahi sonrası 3. ve 6. günde, diğer çalışmada ise sadece ameliyat öncesi toplanan tükürük örnekleriyle ölçülmüştür (18,26).…”
Section: Metodunclassified
“…Tükürük CgA seviyesi ve ortostatik tolerans testi sırasında HRV (Kalp Hızı Değişiminin Spektral Analizi) seviyesi başlangıç, operasyondan 1 saat önce ve operasyondan 1 saat sonra olarak ölçülmüştür. Başlangıç verisi operasyondan önce 2. ve 4. haftalar arası yapılan ölçümlerle oluşturulmuştur (27). Anksiyetenin kalp atım hızı ve oksijen saturasyonu ölçümüyle değerlendirildiği bir çalışmada en düşük kalp atım hızı ve en yüksek oksijen saturasyonu implant cerrahisinden hemen sonra; en yüksek kalp atım hızı ve en düşük oksijen saturasyonu ise implantın yerleştirilmesi sırasında olduğu bulunmuştur (26).…”
Section: Metodunclassified
See 2 more Smart Citations